In good health : uncomplicated, allergen-aware recipes for a nourished life - Riggs, Rachel (Figure 1 Publishing Inc., 2025)
"Rachel Riggs was a specialty food shop owner when her life was upended by chronic illness. Suddenly, she could no longer tolerate any of the foods she'd built a career and life around, requiring her to figure out unfussy dishes with short ingredient lists that were easy to prepare. In her debut cookbook, Riggs shares a personal collection of recipes that celebrate vibrant, healthful eating while being inclusive of many complex dietary needs. In Good Health was developed to empower those with compromised immune systems, chronic illnesses, and food sensitivities with a repertoire of easy-to-prepare, nutrient-dense cuisine that is as delicious as it is nourishing. Riggs expertly eliminates common triggers like gluten, grains, dairy, nightshades, soy, legumes, shellfish, refined sugar, and peanuts while embracing seasonal produce and SoCal sensibilities. Recipes include: A Minty Fresh + Lemony Salad Smoothie for those days you want nutrition but can't bear to stare down a plate of veg. Salads such as Asparagus Mimosa with Tarragon + Orange -- an updated French classic. A slow cooker recipe for French Onion Beef, which freezes magically for later, and can be served over one of the three types of vegetable mash. Scrumptious Mint Chocolate Mini Bundts, approved for all audiences and adaptable for special occasions. These recipes aren't just for those adhering to Mediterranean, Paleo, or Whole30 diets--it will appeal to anyone looking to ditch processed foods, simplify their diet, and take control of their health through nutrition. With a foreword by Dr. Terry Wahls, a leading expert on healing through nutrition, In Good Health is a resource, a celebration, and an invitation to rediscover the power of food in the pursuit of optimal health. "--